1996
DOI: 10.1002/jbmr.5650111005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of parathyroid hormone (hPTH[1-34]) infusion on serum 1,25-dihydroxyvitamin D and parathyroid hormone in normal women

Abstract: Calcium absorption declines with age. Because 1,25-dihydroxyvitamin D (1,25(OH)2D) is the major hormone controlling calcium absorption, changes in vitamin D metabolism may account for the malabsorption of aging. Serum levels of 1,25(OH)2D have been reported to either decrease or remain unchanged with age. To assess the effect of aging on renal production of 1,25(OH)2D, we evaluated the response of renal 25OHD 1 alpha hydroxylase to human parathyroid hormone (hPTH(1-34) stimulation in 119 women ages 25-83 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…Similar reduction in endogenous PTH was observed acutely after TPTD infusion in normal (22) and osteoporotic women (23). iPTH decrease can be attributed to the suppressive effect of TPTD.…”
Section: Discussionsupporting
confidence: 65%
“…Similar reduction in endogenous PTH was observed acutely after TPTD infusion in normal (22) and osteoporotic women (23). iPTH decrease can be attributed to the suppressive effect of TPTD.…”
Section: Discussionsupporting
confidence: 65%
“…Similar decline in endogenous ΡΤΗ was observed acutely after TPTD administration in normal [3] and osteoporotic women [4]. iPTH decrease has to be attributed to the suppressive effect of TPTD, as it seems that the administration of 20 µg TPTD daily is sufficient enough to inhibit endogenous iPTH release from the parathyroid glands; furthermore the aminoterminal end of PTH is probably the part of the molecule that exerts the negative feedback.…”
Section: Discussionmentioning
confidence: 64%
“…In the published literature there is very little evidence on acute changes in endogenous intact PTH (iPTH) levels after TPTD administration [3,4]; on the other hand, there are no data at all on iPTH changes during long-term treatment. The primary aim of this prospective study was to evaluate the acute and chronic effects of intermittent TPTD administration in serum iPTH levels in postmenopausal women with established osteoporosis.…”
mentioning
confidence: 99%
“…In humans, two studies have shown that the capacity of PTH to increase serum 1,25(OH) 2 D levels declines with age [3,4]. In rats, with maturation and aging, the capacity of PTH to stimulate renal 1,25(OH) 2 D production also declines.…”
Section: Introductionmentioning
confidence: 95%